1996
DOI: 10.1002/pssb.2221930121
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐lattice relaxation in diluted magnetic semiconductors

Abstract: The contribution of pairs and triads of nearest-neighbor spins to the spin-lattice relaxation of magnetization is evaluated in Mn-based diluted magnetic semiconductors. Modulation of the exchange interaction by lattice vibrations allows transitions in the cluster which change the total magnetization when the Dzyaloshinski-Monya interaction is taken into account. Spin-lattice relaxation rates are calculated for pairs and open triads due to a two-phonon Orbach process. In Cdl_,Mn,Te it is found that the main con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…In Table 1, this time constant is compared with those measured by the same technique on (Zn,Cd,Mn)Se QWs. The QW data reflect the expected tendency that the SLR rate grows exponentially with the Mn content, caused by the contribution of Mn pairs and higher complexes in the coupling of the Mn spins to the lattice [11]. We emphazise that the values observed on the quarternary (Zn,Cd,Mn)Se QWs match well with data reported for (Zn,Mn)Se QWs [12].…”
Section: Resultssupporting
confidence: 77%
“…In Table 1, this time constant is compared with those measured by the same technique on (Zn,Cd,Mn)Se QWs. The QW data reflect the expected tendency that the SLR rate grows exponentially with the Mn content, caused by the contribution of Mn pairs and higher complexes in the coupling of the Mn spins to the lattice [11]. We emphazise that the values observed on the quarternary (Zn,Cd,Mn)Se QWs match well with data reported for (Zn,Mn)Se QWs [12].…”
Section: Resultssupporting
confidence: 77%
“…The SLR rate is a strong function of the lattice temperature [12], and it decreases weakly in magnetic fields B below 12 T [8-10, 6] but increases rapidly (…”
Section: Introductionmentioning
confidence: 99%
“…1(c) 6,8 . Such a strong dependence is explained by the role of Mn clusters as relaxation centers 9 in the absence of SLR for isolated Mn ions. With increasing Mn concentration the number of clusters grows and the cluster structure evolutes in size involving more and more spins.…”
Section: Introductionmentioning
confidence: 99%
“…Both the number of Mn spins coupled in clusters as well as the typical cluster size progressively increase with growing Mn concentration 22 . This is the reason for the strong dependence of the SLR time on the Mn concentration 9,23,24 . Within the framework of a simple model which accounts for the spin diffusion from Mn ions to Mn clusters, where the spin has an efficient relaxation, it can be shown that the SLR rate 1/τ SLR has a strong dependence on the Mn content with a power law between x 3 and x 4 [11].…”
Section: A Concentration Dependence Of Slr Dynamicsmentioning
confidence: 99%